48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-847
|View full text |Cite
|
Sign up to set email alerts
|

Value Operations Methodology for Value Driven Design: Medium Range Passenger Airliner Validation

Abstract: Abstract:This paper gives insight in the development of a Value Operations Methodology (VOM) that can be used to support Value Driven Design (VDD). The VOM establishes expressions for operational value levers that are incorporated into a weighted value function. This value function is then used to optimize the design variables that are incorporated into it so that the design process is actively driven by value assessments that provide design decision metrics. However, the VOM is generic in nature and has a muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
2
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 3 publications
(2 reference statements)
0
17
0
Order By: Relevance
“…The profitability idea is further cascaded down to the system components, and used to establish requirements at different levels of granularity in the system description. A major challenge in this cross-pollination today is that VDD research neither considers sustainability explicitly, apart from sporadic attempts [218], nor proposes how value "models" can be applied to understand seemingly inconsistent, ill-defined and immature design situations, which are typical of the earliest stages of the design process. These contributions also show how VDD tools may be used to decompose sustainability implications, clarifying how quantitative value assessments may be tighten up with qualitative sustainability analysis by relating them both to the overarching concept of 'value'.…”
Section: Discussionmentioning
confidence: 99%
“…The profitability idea is further cascaded down to the system components, and used to establish requirements at different levels of granularity in the system description. A major challenge in this cross-pollination today is that VDD research neither considers sustainability explicitly, apart from sporadic attempts [218], nor proposes how value "models" can be applied to understand seemingly inconsistent, ill-defined and immature design situations, which are typical of the earliest stages of the design process. These contributions also show how VDD tools may be used to decompose sustainability implications, clarifying how quantitative value assessments may be tighten up with qualitative sustainability analysis by relating them both to the overarching concept of 'value'.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-pollinating sustainability and VDD research remains a challenge today, for two main reasons. Firstly, VDD models do not consider sustainability explicitly, apart from sporadic attempts [221]. Secondly, VDD optimization functions struggle to fit with the earliest innovation process stages, which are characterized by seemingly inconsistent, ill-defined and immature knowledge [222][223].…”
Section: Discussionmentioning
confidence: 99%
“…1 is given by Curran et al 7 in the establishment of their value function for the passenger aircraft, as shown in Eq. 2.…”
Section: Value Operations Methodology (Vom)mentioning
confidence: 99%
“…The Value Operations Methodology (VOM) as proposed by Curran et al 7 is aimed at promoting operational value and ultimate utility as the main criterion to be used in engineering design making. It establishes expressions for operational value levers that can be incorporated into a weighted value function that more accurately captures the true value criterion on which to base engineering and operational decisions.…”
Section: Value Operations Methodology (Vom)mentioning
confidence: 99%
See 1 more Smart Citation